Pertanggungjawaban Pidana Beneficial Owner dalam Tindak Pidana Korupsi yang Dilakukan oleh Korporasi di Indonesia - Mas Putra Zenno Januarsyah; Agustinus Purnomo Hadi; Yogi Muhammad Rahman; Amriyanto; Ahmad Jaeni (Magister of Law, Faculty of Law, University of Mataram, 2026)
Corporate corruption in Indonesia increasingly involves individuals who exercise substantive control over corporations without holding formal positions within their organizational structures. This creates a legal problem because the Criminal Code recognizes beneficial owners as potential subjects of criminal liability but does not provide clear operational parameters for the circumstances under which such liability may be imposed . This study examines the criminal liability of beneficial owners in corporate corruption cases and the legal standards required to attribute individual responsibility. It employs a normative legal research method using statutory, case, and limited comparative approaches. The findings show that beneficial-owner status and the receipt of economic benefits cannot independently establish criminal liability. Liability requires proof of effective control, a clear connection between that control and the corrupt conduct, and individual culpability. The cases of PT Imaji Media, Garuda Indonesia–Rolls Royce, and Pertamina illustrate different forms of control through nominee management, corporate intermediaries, and indirect corporate relationships. Piercing the corporate veil may assist in identifying the individuals behind corporate structures but cannot replace proof of personal involvement in the offense. The study emphasizes the need for clearer legal standards based on effective control, connection with corrupt conduct, individual culpability, and economic benefit as supporting evidence.